2021
DOI: 10.1111/ane.13397
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid and socioeconomic associations in Swedish women with epilepsy 2010–2015

Abstract: Socioeconomic disparities in epilepsy care have been reported across countries and healthcare systems. Persons with epilepsy and low socioeconomic status (SES) seem to have more severe epilepsy, higher rates of emergency visits, hospitalizations, and breakthrough seizures 1,2 compared to persons with high SES. Regarding access to care, low SES has been associated with longer time to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The education level of responders to our survey were both encouraging and disappointing. Forty percent of users of the information module had a university education, which fits very well with the proportion seen in a recent register‐based study of all women with epilepsy without intellectual disability in Sweden 21 . However, 67% of users of the pregnancy module had a university education.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The education level of responders to our survey were both encouraging and disappointing. Forty percent of users of the information module had a university education, which fits very well with the proportion seen in a recent register‐based study of all women with epilepsy without intellectual disability in Sweden 21 . However, 67% of users of the pregnancy module had a university education.…”
Section: Discussionsupporting
confidence: 84%
“…Forty percent of users of the information module had a university education, which fits very well with the proportion seen in a recent register‐based study of all women with epilepsy without intellectual disability in Sweden. 21 However, 67% of users of the pregnancy module had a university education. This could suggest that our system mainly enhances the epilepsy care of patients of a high socioeconomic position.…”
Section: Discussionmentioning
confidence: 99%
“…16 We have studied the use of VPA in women of childbearing age in Sweden on a population-wide scale and found a decreasing use, reflecting increased awareness of negative effects, commencing before the EMA restrictions of 2018. 17 There are also other aspects of the pregnancy prevention programme that have not been assessed in Sweden or Norway. Studies in other countries have for instance found the EMA restrictions to increase use of contraceptive methods in women with VPA for psychiatric indications.…”
Section: Discussionmentioning
confidence: 99%
“…Even when on treatment, disparities in drug choice persist, including in what may be inappropriate care. A population-based study of women living in Sweden aged 18–45 years between 2010 and 2015, with a diagnosis of epilepsy and no intellectual disability ( n = 9143) found socioeconomic differences in the frequency of valproic acid (VPA) prescription [6]. Guidelines in Europe (and around the world) suggest that VPA should be avoided in women of child-bearing age.…”
Section: Epilepsy Diagnosis Ambulatory Care and Medication Initiationmentioning
confidence: 99%